Implant loosening after total knee replacement with pigmented villonodular synovitis: a case report - Hajar Azizah Armarani Mallapasi; Fidelis Heru Wicaksono; Riza Aprizal (Surgical Residency Program Syiah Kuala University, 2026)
Introduction: Aseptic loosening after total knee replacement (TKR) defined as prosthesis loosening from bone along with macrophage-induced inflammatory response without infection or trauma that may arises due to gradual mechanical loss of fixation while pigmented villonodular synovitis (PVNS) refers to a benign disease arises from synovium. Although the etiology of PVNS remains unclear and the underlying cause of PVNS occurrence following total knee replacement are limited in publication studies, a hypothesis of microtrauma causing recurrent hemorrhage may lead to PVNS. To date, there is no clear consensus on the primary treatment option for PVNS and surgery is generally the primary approach. Surgical excision with total synovectomy is considered to be the gold standard for PVNS. Case description: A 63-year-old woman with a history of left total knee replacement (TKR) 3 years prior came to our center with initial complaints of persistent pain and progressive impairment of daily activities. The patient later underwent a revision procedure along with open synovectomy due to suspected PVNS finding which confirmed with histopathological studies. Three months postoperatively, the patient showed marked improvement of left knee range of motion and quality of life measured with KOOS scoring of 78 out of 100. Conclusion: This case presenting an aseptic loosening after total knee replacement accompanied by PVNS finding confirmed by histopathologic studies. Implant loosening is thought to be related to loss of mechanical fixation or chronic inflammation, while PVNS occurrence following the implant loosening is likely triggered by microtrauma.